2021
DOI: 10.15575/psy.v7i2.5713
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling Intervention on Prosocial Behavior Improvement among Early Childhood

Abstract: The prosocial behavior in childhood needs to develop because it is associated with favorable developmental outcomes in later hood. Digital storytelling is a method that assumed can help in encouraging and improving social behavior. It is combined digital media, including text, images, music and video. Digital storytelling can effectively improve prosocial behavior as opposed to the traditional storytelling approach. This study aims to examine and explore the effect of digital storytelling intervention methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
2
2
0
2
Order By: Relevance
“…Fairy tales can increase prosocial behaviour and reduce aggressive behaviour in kindergarten children [22]. This research is in line with research conducted by Aisha et al [23]; one of the benefits of storytelling is increasing children's prosocial behavior.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Fairy tales can increase prosocial behaviour and reduce aggressive behaviour in kindergarten children [22]. This research is in line with research conducted by Aisha et al [23]; one of the benefits of storytelling is increasing children's prosocial behavior.…”
Section: Introductionsupporting
confidence: 85%
“…The moral messages and teachings of characters in these fairy tales can serve as examples to create even better behaviour. Storytelling is not only retelling but can also express feelings and thoughts verbally [23]. However, this storytelling requires a relatively long time for its application in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence of any anxiety disorder among children according to the Diagnostic and Statistical Manual (DSM) and the International Statistical Classification of Diseases and Associated Health Problems (ICD) has been shown to be 6.5% in children aged 11-12 years [2]. This is in line with the research of [10]. who found that younger children seemed more free to express themselves and their thoughts, whereas older children felt embarrassed if they had to express themselves and their own feelings which made them appear less confident.…”
Section: Demographic Characteristics Among School-age Childrensupporting
confidence: 71%
“…In addition, presenting stories using audio-visual media can help build children's absorption, or ability to hold their attention, as well as their creativity and ability to create exciting scenarios. Using DS to teach children is to develop their empathy, perspective-taking, self-awareness, and sense of community (Aisha & Kaloeti, 2021). The use of digital media in early childhood learning through DS helps develop children's digital literacy skills, which are very important for future education (Maureen et al, 2021).…”
Section: Rq1 What Is the Urgency Of Digital Storytelling In Early Chi...mentioning
confidence: 99%